Analyzing Mispronunciation Errors in English Learning and Teaching - Hafizh Nurul Huda; Ratna Dewanti (Universitas Cokroaminoto Palopo, 2022)
There has been much discussion about how errors affect students' language proficiency, but few research have specifically examined teacher errors. The error that is passed down from the teacher, meantime, is one of the major reasons why students make mistakes. In order to avoid mistakes when instructing in elementary schools about the ideal time for pupils to acquire and learn a foreign language, EFL teachers must take into account the habit that students have of mimicking their teacher's voice production. This study investigates the pronunciation errors of EFL teachers, in particular to find out the form and causes of pronunciation errors in the vowels produced by the teacher. The participant of this study was a selected English teacher from an elementary school in Pandeglang who was invited to pronounce 62 English words. Teachers are also asked to fill out a questionnaire to find out what external factors are thought to trigger errors. The findings illustrate that teachers produce various forms of pronunciation errors in English vowels. The causes of errors lie in interlingual transfer, intralingual transfer, pronunciation differences between graphemes and sounds, hypercorrection, and word similarity. External factors were also investigated, which included educational background and teacher's lack of English practice. This study suggests that elementary EFL teachers in Indonesia should improve their pronunciation by practicing frequently and having intensive pronunciation training to teach better English to their students.